Discovery of Pseudancylis Horak, 2006 with description of new species and documenting two additional species records (Lepidoptera: Tortricidae) from India - V.S. Aashiq Poon; Karthik M. Reddy; Santhosh Naik; S.S. Anooj; Pathour R. Shashank (Journal of Asia-Pacific Biodiversity)
Genus Pseudancylis Horak, 2006 is recorded for the first time from India with the description of new species Pseudancylis kodaguensis Shashank sp. nov., and an annotated checklist of all species under the genus is provided. Additionally, two Enarmoniini species, namely Taiwancylis cladodium Razowski, 2000 and Anathamna megalozona Meyrick, 1916 are recorded for the first time from India with descriptions and photographic illustrations.